Anatomically Standardized Maps Reveal Distinct Patterns of Cartilage Thickness With Increasing Severity of Medial Compartment Knee Osteoarthritis. Issue 11 (2nd May 2017) - Favre, Julien; Erhart‐Hledik, Jennifer C.; Blazek, Katerina; Fasel, Benedikt; Gold, Garry E.; Andriacchi, Thomas P.
ABSTRACT: While cartilage thickness alterations are a central element of knee osteoarthritis (OA), differences among disease stages are still incompletely understood. This study aimed to quantify the spatial‐variations in cartilage thickness using anatomically standardized thickness maps and test if there are characteristic patterns in patients with different stages of medial compartment knee OA. Magnetic resonance images were acquired for 75 non‐OA and 100 OA knees of varying severities (Kellgren and Lawrence (KL) scores 1–4). Three‐dimensional cartilage models were reconstructed and a shape matching technique was applied to convert the models into two‐dimensional anatomically standardized thickness maps. Difference thickness maps and statistical parametric mapping were used to compare the four OA and the non‐OA subgroups. This analysis showed distinct thickness patterns for each clinical stage that formed a coherent succession from the non‐OA to the KL 4 subgroups. Interestingly, the only significant difference for early stage (KL 1) was thicker femoral cartilage. With increase in disease severity, typical patterns developed, including thinner cartilage in the anterior area of the medial condyle (significant for KL 3 and 4) and thicker cartilage in the posterior area of the medial and lateral condyles (significant for all OA subgroups). The tibial patterns mainly consisted of thinner cartilage for both medial and lateral compartments (significant for KL 2–4). Comparing anatomically standardized maps allowed identifying patterns of thickening and thinning over the entire cartilage surface, consequently improving the characterization of thickness differences associated with OA. The results also highlighted the value of anatomically standardized maps to analyze spatial variations in cartilage thickness. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:2442–2451, 2017.